2022
DOI: 10.3390/ani12212998
|View full text |Cite
|
Sign up to set email alerts
|

Garlic and Its Bioactive Compounds: Implications for Methane Emissions and Ruminant Nutrition

Abstract: Methane (CH4) emission from enteric fermentation of ruminant livestock is a source of greenhouse gases (GHG) and has become a significant concern for global warming. Enteric methane emission is also associated with poor feed efficiency. Therefore, research has focused on identifying dietary mitigation strategies to decrease CH4 emissions from ruminants. In recent years, plant-derived bioactive compounds have been investigated for their potential to reduce CH4 emissions from ruminant livestock. The organosulphu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 137 publications
2
10
0
Order By: Relevance
“…Its relative feeding value resembles silage maize, establishing it as an excellent unconventional roughage [25]. This study further demonstrated that including 60% garlic straw significantly enhanced dry matter digestibility, aligning with prior research [19,26].…”
Section: Effects Of Different Addition Ratios On In Vitro Gas Product...supporting
confidence: 86%
See 2 more Smart Citations
“…Its relative feeding value resembles silage maize, establishing it as an excellent unconventional roughage [25]. This study further demonstrated that including 60% garlic straw significantly enhanced dry matter digestibility, aligning with prior research [19,26].…”
Section: Effects Of Different Addition Ratios On In Vitro Gas Product...supporting
confidence: 86%
“…The incorporation of garlic straw impacts various indicators, with gas production as a pivotal measure of rumen fermentation activity, providing insight into the action of rumen microorganisms. While previous research indicated that substances derived from garlic, such as garlic leaf [14], garlic powder [15][16][17], garlic oil [18], allicin [19], and other extracts were able to reduce methane production, our study yielded consistent results in the G80 group. Specifically, the addition of silage garlic straw led to an increase in the rumen gas production in Hu sheep.…”
Section: Effects Of Different Addition Ratios On In Vitro Gas Product...supporting
confidence: 59%
See 1 more Smart Citation
“…Thus, T1 which contained the highest concentration of garlic foliage (i.e. also sulphur compounds), was expected to show a higher antiprotozoal activity, and in consequence, lower methanogenesis due to reduced transfer of hydrogens, as detailed earlier (Sari et al, 2022). On the other hand, if garlic foliage and methanogenesis suppressors were reduced, a higher protozoal activity should be expected, and indeed it was observed in T4.…”
Section: In Vitro Gas Productionmentioning
confidence: 66%
“…The digestive system of ruminants mainly comprises the rumen, reticulum, omasum, and abomasum (Sari et al, 2022). Rumen is the most important and largest chamber that harbors a large number of microorganisms (Paswan et al, 2022).…”
Section: Anti-protozoal Activity Of Garlic In Rumi-nantsmentioning
confidence: 99%